Sejarah Perkembangan Islam di Iran - Rais, Muhammad (Tasamuh: Jurnal Studi Islam, 2018)
In the 1935 the name of Persia was succeeded by Iran, and then in Revolution 1979, Iran was became Islamic Republic of Iran state (al-Jumhuria al-Islamia Iran). Ayatullah Khomeini as revolutionary leader and Syiah figure was successfully lead the Iran State to fuse between modern and al-Imam conception (Imamiyah). The paper will describe the existence of Islam in history of Iran before and after Iran Revolution in 1979. The development of Islam in Iran more related to the Syiah that dominated in population, politics, social order, and so forth. Iran population (in 2000) amount to 159.051.000 people, that 93% is Syiah, 5% Sunni, and 2% the others. It means the number of Syiah population that juridical Iran as Islamic State of Syiah. Therefore, to know about the history of Islam in Iran, we must to understand of the Syiah. In other word, the development of Islam in Iran is related to the development of Syiah in Iran, because of prescribed by the rules of qanun (legal statute of Iran) after Iran Revolution (1979) was based on mazhab Syiah, is Wilāyat al-Faqīh. However, upon Ayatullah Khomeini death, on June 3rd 1989, after Gulf War, Ali Khomeini successes to the government. Under his government, Ali Khomaeini which involves the ulama reforms the characters of liberal Western to Islamic in social order of society